## Thursday, April 30, 2015

## Friday, April 24, 2015

## Wednesday, April 22, 2015

## Tuesday, April 21, 2015

## Monday, April 20, 2015

## Sunday, April 19, 2015

## Thursday, April 16, 2015

## Tuesday, April 7, 2015

## Saturday, April 4, 2015

You can solve this system by substituting 2y+3 for x in the second equation. The second equation becomes 3(2y+3) + 4y = 16. Now we can solve for y.

6y + 9 + 4y = 16

10y = 7

y = 7/10

To solve for x, substitute 7/10 for y in the first equation. That gives us

x = 2(7/10) + 3

x = 14/10 + 3

x = 4.4

Subscribe to:
Posts (Atom)